Kinerja Karyawan Hotel Dalam Meningkatkan Occupancy Tamu Di Hotel Lilik Dagen Yogyakarta - Budi Lestari dan Wisnu Hadi (Universitas Bina Sarana Informatika, 2013)
Tourism world is the wold’s universal meaning that anyone would claim that tourism was primary human needs worldwide. Along with the increase in welfare and prosperity of a nation in economic, emerge from human nature is a desire to see the other side of the world of difference to everyday life, in term of cultural, customary, daily living habits and creates naturel which differentiated by the omnipotent that causes a person’s curiosity of people saw and enjoyed it. This thesis aims to find out hotel employee perfomance and determining guest occupancy level at Hotel Lilik Dagen, Yogyakarta. Where in this discussion presented employees perfomances at Hotel Lilik Dagen for each department are grouped into twofactors that is internal and external factor. These factors will be synergy with job satisfaction level that influence employee perfomances to the guest or room occupancy level of Hotel Lilik Dagen, Yogyakarta. From the both of analysis factors of employees perfomance at Hotel Lilik Dagen, Yogyakarta influences by internal factor that is employees perfomance in all department, where the operational activity conducted in hotel areas directly to increase guest occupancy that are Housekeeping, Front Office, and Restaurant Department. While, to the external factor is all deparment of employees perfomance, where its operational activity to public. It conducted by Marketing Department to increase guest occupancy at Hotel Lilik Dagen, Yogyakarta. In order to increase guest occupancy, employee perfomance to meet some constraints, which constraints the employees perfomance at Hotel Lilik Dagen is Naturally more internal technical and solution depends on the management policy of the hotel itself. The factors that determined guest occupancy level at Hotel Lilik Dagen, Yogyakarta is hotel’s strategic lication, a satisfactory system for guest service, and atmosphere of intimacy that exist between the guest with the hotel employees like family. Keyword: hotel employee perfomance, guest occupancy